PERTIMBANGAN HAKIM PADA PUTUSAN PEMIDANAAN KEPADA PELAKU TINDAK PIDANA ILLEGAL FISHING DI WILAYAH ZONA EKONOMI EKSKLUSIF INDONESIA (Studi Putusan Nomor 314/Pid.Sus/2017/PN Bls) - Deniati Buulolo (Jurnal Panah Hukum, 2023)
Illegal fishing is an act of catching fish or illegal fishing activities carried out by a person or certain groups whose activities are not reported to an authorized institution or agency. This study aims to find out, understand and analyze the judge's considerations in sentencing decisions against perpetrators of illegal fishing in the Indonesian Exclusive Economic Zone (study of decision number 314/Pid.Sus/2017/PN Bls). The research used is normative research with data collection techniques using primary data, secondary data, and tertiary data. Based on research findings and discussion of judges' considerations in sentencing decisions against illegal fishing perpetrators, it is known that the panel of judges has considered several things. Therefore, the perpetrators were found guilty. In decision number 314/Pid.Sus/2017/PN Bls, the panel of judges did not apply the cumulative penalty as determined and threatened in the relevant article. The judge's consideration of only imposing fines on the perpetrators, according to the author's view, the sentencing decision was inappropriate because there was no reason to abolish or abolish imprisonment and did not give a deterrent effect to the perpetrators, where a deterrent effect is one of the goals of punishment. So, according to the author, in decision number 314/Pid.Sus/2017/PN Bls, prison sentences should have been applied to the defendants so that the legal objectives themselves could be achieved